Kyrgyz Republic : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1999)
This paper reviews economic developments in the Kyrgyz Republic during 1995-99. After having contracted by about 50 percent between 1992 and 1995, real GDP recovered strongly in 1996, with a growth rate of more than 7 percent. The main source behind this increase was a strong growth of the agricultural sector, which continued the following year, and, combined with the startup of the Kumtor gold mine, led to a real GDP growth rate of almost 10 percent in 1997. During 1998, growth slowed down to about 2 percent.